Simulation Study of Topological Structures and Node Coordinations for Deterministic WSN with TSCH - Vijaya Perumalla; B. Seetha Ramanjaneyulu; Ashok Kolli (Society of Visual Informatics, 2017)
Time-Slotted Channel hopping (TSCH) that was introduced in IEEE802.15.4e is a promising technique to offer deterministic data deliveries in Wireless Sensor Networks (WSN). Its main strength lies in using multiple channels for the transmissions, using frequency hopping method. However, it takes more time for initializing the network, as beacons have to be released on multiple frequencies and scanning needs to be carried out by the devices in all those frequencies for joining the network. In this work, a simulation study is carried out to investigate the effect of these delays for different types of multihop networks. The benefit of introducing multiple coordinators in reducing these time delays is also studied. It is found that the delays are increasing linearly with the number of hops in the network and adding an additional coordinator can bring down the initialization time by half.